Me Pengaruh Konseling Individu Dengan Pendekatan Gestalt Teknik Kursi Kosong Terhadap Peningkatan Perilaku Asertif Siswa Korban Bullying: Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan, Daftar Pustaka - Nadaa Alya Salsabilla; Rita Sinthia; Mayang T. Afriwilda (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
This study was conducted with the aim of knowing how the effect of individual counseling with the gestalt approach of empty chair technique on increasing the assertive behavior of students who are victims of bullying. This study used qualitative research methods with the subjects AM and KH. Data collection was carried out by observation, interview and documentation. Data analysis through data reduction, data presentation and conclusion drawing. Providing individual counseling with a gestalt approach to empty chair techniques as a form of increasing the assertive behavior of students who are victims of bullying. The results showed that the assertive behavior of the subject could increase. Such as being able to be open and honest with yourself and others, being able to defend your rights, being able to express your disagreement with something, being able to deal with bullies. From the results of this study, it is suggested to counseling teachers to improve the assertive behavior of students who are victims of bullying using individual counseling services with an empty chair gestalt approach. Keywords: individual counseling, gestalt, assertive behavior, bullying, empty chair